Cardiovascular risk factors in a Roma sample population from Romania - Weiss Emma; Japie Cristina; Balahura Ana Maria; Bartos Daniela; Badila Elisabeta (Sciendo, 2018)
Background. The Roma population has a high prevalence of cardiovascular risk factors, higher mortality, and shorter life expectancy. It is found in the largest number in Romania, but published data are still scarce here. We studied cardiovascular risk factors and disease along with target organ damage on a population of Roma inhabitants from Bucharest, Romania.